KETRAMPILAN MEM8ACA SISWA SEKOLAH DASAR DENGAN PENDEKATAN PROSES - Syamsi, Kastam (Jurnal Cakrawala Pendidikan, 2016)
The purpose 01" this study are (I) 1:0 ltnprove the elclllClllary school sl’udcnts’attitudc t()teaching rC(lding and (2) to ilnprove the elerncHtary school tudcnts rcading skills. This study was held at the students of grade 4 and 5 of l 1 inonlartani 3 Elementary School Yogyakarta.. T’he actions process is carried out’ in on cycle. Oeut;raUy, this sluuywas al’rallg tI as followed: (1) the goal: finding the approach in order to improve the elementary school students attitude toward teaching reading and to improve the elenlentary school students reading skill, (2) time: 14 classes meeting, (3) person: lecture, two Indonesian grade fuurthanu fifth l achc,., (4) gcn ral actiun: planning lhus an. (a) itlClllifyillg reading and (b) arranging the action, implementing the action (that is the use of a reading process approach in teachingreading including the steps of preparing to read, reading, responding, exploring the tcxt, and extending the interpretation), monitoring and evaluation, and reflecting. The monitoring instrulnents is observation sheet and field note, whereas theinstrumen of evaluation are reading test and questioner. rhe result ofthis study are (I) basically the reading proccss approach in tcaching rcading is able to improve the elementary school students’reading skill and their attitude toward teaching reading, (2) at the first step of reading process the student did not have opportunities to choose the text themselves, and (3) the impacts of the inlplementing the action is students have participate at speaking and writing activities so they can improve their language skills